2023
DOI: 10.24815/jpsi.v11i1.26790
|View full text |Cite
|
Sign up to set email alerts
|

Ethnochemistry: Exploring the Potential of Sasak and Javanese Local Wisdom as a Source of Chemistry Learning to Improve the Learning Outcomes of Pre-Service Teachers

Abstract: Learning resource availability was still focused on abstract concepts without integrating them with students' daily experiences. This appears since the ethnochemistry approach implementation in universities is still rarely conducted.  The purpose of this study is to analyze the relevance of Sasak and Java local wisdom with chemistry and explore the potential of Sasak and Java local wisdom as a learning resource in basic chemistry courses. The data collection instruments were observation, interviews, and docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The findings of this study are expected to contribute to chemistry learning innovation. In addition, this research agrees that learning chemistry can be more engaging, meaningful and fun if presented in concrete examples that often occur in students' daily lives (Santos & Arroio, 2016;Wahyudiati, 2016;Wahyudiati, 2023).…”
Section: Recommendationssupporting
confidence: 68%
See 1 more Smart Citation
“…The findings of this study are expected to contribute to chemistry learning innovation. In addition, this research agrees that learning chemistry can be more engaging, meaningful and fun if presented in concrete examples that often occur in students' daily lives (Santos & Arroio, 2016;Wahyudiati, 2016;Wahyudiati, 2023).…”
Section: Recommendationssupporting
confidence: 68%
“…The results of previous research showed that the application of an ethnochemistry approach in the learning process, either through integration with learning models or as a source of learning for scientific investigations, as well as as a natural laboratory, can develop students' abilities to think critically, skills in carrying out scientific processes, and learning outcomes. Therefore, students' cognitive abilities can be improved (Ador, 2017;Wahyudiati, 2020;Wahyudiati & Fitriani, 2021;Wahyudiati & Qurniati, 2023). Exploring the potential of Samawa's local wisdom as an innovation in chemistry learning could grow the younger generation's love for their culture.…”
Section: Recommendationsmentioning
confidence: 99%
“…The development of learning games that consider local culture is not only an effective way to increase students' interest and participation in learning but also an effort to introduce and maintain cultural values for the younger generation. The integration of local culture into science learning is also expected to positively in uence students' development in accordance with Vygotsky's theory on the importance of social and cultural experiences in education (Wahyudiati & Qurniati, 2023). Therefore, this research offers an innovative approach and has the potential to improve the science learning outcomes of Grade IV primary school students, as well as contributing to the preservation and appreciation of local Papuan culture.…”
Section: Literature Reviewmentioning
confidence: 62%
“…Students may not have adequate access to technological devices or lack an understanding of how to use technology in chemistry learning (Zubaidah, 2019). Second, a curriculum that does not emphasize the integration of technology with local wisdom is also a factor causing this problem ( (Papilaya & Tuapattinaya, 2022); (Wahyudiati & Qurniati, 2023)) If the existing curriculum does not pay attention to the importance of integration between technology and local wisdom in chemistry learning, then students will have difficulty developing relevant and applicable understanding (Deviana & Sulistyani, 2021). Third, the teacher's inability to integrate technology and local wisdom also contributes to this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from that, it is also important to incorporate local wisdom into the context of chemistry learning (Hanum, 2020). Integrating local wisdom in chemistry learning can provide real and relevant context for students, increasing the connection between chemical concepts and their environment and culture (Wahyudiati & Qurniati, 2023).…”
Section: Introductionmentioning
confidence: 99%